CRISPR-based modular assembly of a UAS-cDNA/ORF plasmid library for more than 5500 Drosophila genes conserved in humans - Wei, Ping; Xue, Wen; Zhao, Yun; Ning, Guang; Wang, Jiwu

(untitled) (Genome Research, 2020)
Construction of a genome-wide transgenic UAS-cDNA/ORF library in Drosophila based on the binary GAL4/UAS system has been severely hampered by technical difficulties, although genome-wide cDNA or ORF resources of Drosophila, human, and mouse have been publicly available for more than a decade. Here, we developed a new method named CRISPR-based modular assembly (CRISPRmass) for the high-throughput construction of a genome-wide UAS-cDNA/ORF library from publicly available cDNA/ORF resources. Through cleavage of shared vector sequences of cDNA/ORF plasmids by CRISPR/Cas9 and subsequent insertion of UAS modules by Gibson assembly, the procedure of construction of such a library by CRISPRmass is standardized as massively parallel two-step test tube reactions before bacterial transformation. Using CRISPRmass, we generated 5551 UAS-cDNA/ORF constructs covering 83% of the Drosophila genes conserved in humans in the Drosophila Genomics Resource Center (DGRC) Gold Collection, and among them, 5518 were generated within 3 mo by three people. Our results show that CRISPRmass allows modulization, simplicity, efficiency, and adaptability in the generation of a genome-wide UAS-cDNA/ORF plasmid library by using publicly available cDNA/ORF resources. CRISPRmass can be applied to editing various genome-wide libraries in general and is an alternative to Gateway technology in high-throughput plasmid library editing. Furthermore, the more than 5500 UAS-cDNA/ORF plasmids of Drosophila genes serve as a powerful resource for gain-of-function (GOF) screening in cultured cells and for generation of a transgenic UAS-cDNA/ORF library in Drosophila.